Um olhar diferente sobre a Branca de Neve e os sete anões: um recurso didático sobre o funcionamento mental - SILVA, Waldine Viana da (Universidade Federal do Pará, 2017)
In this study we emphasise the personality caractheristics, tryingto amplify the mental functioning matter facing the richness of a work based on a tale. We aim to worth the mental functioning of each dwarf as a personality envolved on na emocional drama, exploded by the jelousy of the stepmother about the youth and beauty teeanage stepdaugther. On the other hand, we expect this theme can be used as didatic resourse about the mental functioning, serving as a practical, simple and dinamic guide for the professor in classroom, as for Psychiatric Nursing as for Medicine ones, specializing on Psychiatry, in their initial learnig phase.